(3CLed fcJIs - (3aQGL, CMeOs ((3GdLjRI, eUQs (3OGQ GdaGQhbs, 2010)
(3fbOe ai gPG GdcJGH eLehYI ef GdfcGJ GdTGFbI hbO cJHfGgG HdZI SgdI hGVMIs
(3bUU acGgjIs
1 4 5 6 7 12 13 14
Keywords: Humorous stories; (3GdbUU GdacGgjIs